Tasawuf dan Pengembangan Diri: Upaya Optimalisasi Karakter dan Potensi Manusia Secara Holistik - Alfiah, Nur; Noor, Afwan Maula; Farhan, Ahmad; Furqon, Ahmad (Journal of Sufism and Psychotherapy, 2024)
This research highlights how the concepts of Sufism can guide the holistic development of human character and potential. In the modern context, this approach is often associated with “self-improvement” or self-development that aims to achieve a higher quality of life, spiritually, mentally and socially. Qualitative research with a descriptive-analytical approach is used to understand, describe, and analyse the concepts of Sufism related to self-development. Literature study is also used to explore classical Sufism works and their relevance to modern studies. The results show that there are key aspects of the relationship between Sufism and self-development, namely Tazkiyatun Nafs (Purification of the Soul), Muraqabah (Full Awareness of God's Presence), Mujahadah (Effort and Self-Control), Ihsan (Perfection in Doing Good), and Spiritual and Worldly Balance. Each of these key concepts can be used as an effort in optimizing human character and potential holistically. Especially if the implementation of the five key concepts is preceded by Awaluddin Makrifatullah as the main foundation in tasawuf, it will further strengthen efforts to optimise the character and potential of an individual holistically. This is because, awaluddin makrifatullah is the main key for an individual to be able to understand holistically and comprehensively about the meaning of life, including understanding the existence of humans and all His creations, both visible and invisible (ghaib) in this world.